Histopathological survey of putative parasites and pathogens in non-native slipper limpets Crepidula fornicata - Emma Quinn (Diseases of Aquatic Organisms, 2023)
Two populations of the invasive slipper limpet Crepidula fornicata were sampled in Swansea Bay and Milford Haven, Wales, UK, to determine the presence of putative pathogens and parasites known to affect co-located commercially important shellfish (e.g. oysters). A multi-resource screen, including molecular and histological diagnoses, was used to assess 1800 individuals over 12 mo for microparasites, notably haplosporidians, microsporidians and paramyxids. Although initial PCR-based methods suggested the presence of these microparasites, there was no evidence of infection when assessed histologically, or when all PCR amplicons (n = 294) were sequenced. Whole tissue histology of 305 individuals revealed turbellarians in the lumen of the alimentary canal, in addition to unusual cells of unknown origin in the epithelial lining. In total, 6% of C. fornicata screened histologically harboured turbellarians, and approximately 33% contained the abnormal cells—so named due to their altered cytoplasm and condensed chromatin. A small number of limpets (~1%) also had pathologies in the digestive gland including tubule necrosis, haemocytic infiltration and sloughed cells in the tubule lumen. Overall, these data suggest that C. fornicata are not susceptible to substantive infections by microparasites outside of their native range, which may contribute in part to their invasion success.